2014
DOI: 10.1590/1414-462x201400030008
|View full text |Cite
|
Sign up to set email alerts
|

Atitudes de usuários de restaurante "self-service": um risco a mais para a contaminação alimentar

Abstract: Cad. Saúde Colet., 2014, Rio de Janeiro, 22 (3): 266-74 ResumoObjetivo: Avaliar as atitudes de risco dos usuários no momento em que se servem em restaurantes com distribuição "self-service" classes A e B. Métodos: Estudo exploratório realizado com técnica de observação não participante. Para seleção dos restaurantes utilizou-se dois critérios, o primeiro determinado pela variável valor do kg e o segundo utilizando atributos que podem classificar o tipo de serviço. Para avaliar as atitudes de risco dos usuários… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…Studies of attitudes on self-service buffets have shown that consumers engage in unsanitary behaviors [16][17][18]. Among the types of restaurants, self-service poses unique problems because foods are displayed to customers, and there is little (if any) control with hands, clothing, dirt, and droplets that may contaminate foods and utensils [13,14,19]. There is the need for rigorous control of the period the dishes are exposed and their temperatures.…”
Section: Self-service Buffet Restaurants and The Potential Risk Of Contaminationmentioning
confidence: 99%
“…Studies of attitudes on self-service buffets have shown that consumers engage in unsanitary behaviors [16][17][18]. Among the types of restaurants, self-service poses unique problems because foods are displayed to customers, and there is little (if any) control with hands, clothing, dirt, and droplets that may contaminate foods and utensils [13,14,19]. There is the need for rigorous control of the period the dishes are exposed and their temperatures.…”
Section: Self-service Buffet Restaurants and The Potential Risk Of Contaminationmentioning
confidence: 99%
“…Handlers' behaviors and attitudes repeated themselves in the assessed locations: speaking and eating during food handling; resistance/lack of attention to the hand washing protocol, precarious personal presentation, among others 26 . Food service users also help contamination, since, most of the time, they do not sanitize their hands before getting close to the distribution counter, they talk while they serve their plate and use utensils available for food preparation to organize food on their plates 29 . By taking into consideration the comparison proportions, similar conditions regarding -either production facilities and flow of employees and customers -were observed in free fairs, supermarkets and restaurants 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Nesse cenário de cuidados em torno da produção de refeições seguras e nutricionalmente adequadas, é preciso garantir a segurança alimentar dos consumidores de refeições em ambientes coletivos. O estudo de Zandonadi et al (2007) tem sido referência para outros que investigam os comportamentos de risco de usuários de restaurantes em diferentes localidades e condições (BANCZEK et al, 2010;BARBOSA et al, 2012;CARVALHO et al, 2012;HENRIQUES et al, 2014).…”
Section: Introductionunclassified